SOSIALISASI PENCEGAHAN DAN DAMPAK PERNIKAHAN USIA DINI DI SMPN 05 KOTO BALINGKA KAB. PASAMAN BARAT: - - Desi Safitri (Journal of Community Dedication and Development (Pengabdian Kepada Masyarakat), 2024)
Early marriage is an increasingly worrying phenomenon in Indonesia, which has serious implications for health, psychology and social welfare. In accordance with Law Number 16 of 2019, the minimum age for marriage is 19 years for men and 16 years for women. However, marriage often occurs at this age, often driven by economic factors, social pressure, and cultural norms that view marriage as a solution to avoid promiscuity. Health Impacts Early marriage poses high health risks to women and their unborn children. Mothers who marry at a young age are at risk of experiencing complications during childbirth, such as bleeding and preeclampsia, and the risk of death is five times greater than mothers who marry at an older age. Children of young mothers are also at risk of experiencing disabilities and stunting. From a psychological perspective, teenagers who marry early often experience emotional instability and find it difficult to carry out their role as parents. This can cause discord in the family and increase the risk of divorce. The inability to manage stress and emotions can have a negative impact on parenting and create an unstable family environment. Socioeconomic Impact From a socio-economic perspective, couples who marry early tend to be less prepared financially and emotionally. Many of them drop out of school, reducing future employment opportunities. As a result, early marriage often worsens the cycle of poverty in society. Prevention Prevention of early marriage requires joint efforts between the government, society and educational institutions. Sex education and awareness of children's rights need to be strengthened so that the younger generation understands the impact of early marriage. Parental and community support is also important in creating an environment that supports teenagers' decisions to postpone marriage until adulthood.